Burnout in Digital Era: The Role of ICT Demands, ICT Resources, and Digital Overload in Public Sector - Melinda Erida Damasari; Elok Savitri Pusparini (Smart Society, 2025)
The increasing integration of digital technologies in public sector work has transformed how employees interact, access information, and perform tasks. While this digital transformation offers efficiency and flexibility, it also introduces new forms of work-related pressure, such as information overload, frequent interruptions, and the need for constant availability. Within the framework of the Job Demands-Resources (JD-R) model, these factors are categorized as ICT demands and ICT resources. The present study investigates how these two dimensions influence employee burnout, while also exploring the mediating role of digital overload in this relationship. Using a cross-sectional design, data were collected from 358 employees in Indonesia’s public education sector and analyzed through structural equation modeling. The findings show that ICT demands have a significant positive effect on both digital overload and burnout, while ICT resources have a significant negative effect on both outcomes. Furthermore, digital overload partially mediates the relationship between both ICT demands and ICT resources with burnout. These results emphasize the dual role of digital technology in shaping employee well-being: while excessive ICT demands can lead to overload and burnout, adequate ICT resources can serve as protective factors. This highlights the importance of balancing digital expectations with supportive infrastructure to promote sustainable and healthy work environments in the public sector.